Transformasi Digital Dalam Manajemen Persuratan Terhadap Perubahan Proses dan Peran Teknologi - Darmansah, Tengku; Br.Lubis, Melati; Hasanah, Uswatun; Sembiring, Desi Fitriyani; Ramadhani, Putri Suci; Br. Lubis, Dessy Masliani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Digital transformation has brought significant changes in various aspects of the organization, including management management. This study aims to review the impact of digital transformation on the change in processes and roles of technology in management management. The research method used is the literature study and analysis of case studies in several organizations that have implemented deditalization of confurtion. The results showed that digitization in management management not only increased efficiency and accuracy in document management, but also accelerated workflow and reduced operational costs. Technology such as digital document management systems, electronic signatures, and collaboration platforms are key factors that encourage effectiveness in management management. This study concluded that digital transformation is an essential strategic step for organizations to remain competitive in the digital era, with significant implications for increasing productivity and quality of service. Recommendations for further implementation include increasing technology infrastructure and staff training to ensure optimal adaptation to this change.